Choice of biopsy devices for post-mortem CT-guided biopsy. (June 2016) - Higgins, Samantha; Parsons, Sarah; Woodford, Noel; Briggs, Christopher; Cauchi, David; O'Donnell, Chris
Abstract: Aim: To assess technical features of multiple biopsy devices for post-mortem CT-guided biopsy (PMCTB). Methods: Five different BARD® clinical biopsy devices, including spring-loaded and vacuum-assisted, were used to perform percutaneous biopsy of the liver in a deceased person using the largest gauge needle size available in each. A standard co-axial biopsy technique was used for all devices except SenoRX®. Specimens were placed on sponge in cassettes for initial fixation and then processed using routine histological techniques. The devices were assessed by a team consisting of a forensic technician, forensic radiologist and two forensic pathologists (one blinded to the type of device used). Assessment parameters included technical performance, cost of device, and specimen review under light microscopy. Results/discussion: The Max-core® and Magnum® devices were mechanically easy to load, fire and retrieve specimens. The Finesse® and Vacora® provided advanced technical features. On histological review the tissue sample from the Vacora® was judged to be of higher quality. Due to the permanent needle attachment to the vacuum machine, the SenoRX® was deemed impractical. Histological artefacts identified included stretch-crush cellular damage likely from the use of vacuum-assisted devices, and tissue breakage from the use of cassette sponges. Conclusion: The 2 spring-loaded biopsy devices are considered the most appropriate for PMCTB tissue sampling based on ease-of-use, lowest cost and provision of diagnosable biopsy specimens. Highlights: 5 core biopsy needle devices were compared for biopsy of the liver in a cadaver. Devices were both spring-loaded and vacuum-assisted. Parameters of assessment included ease-of-use, cost and histological quality. Spring-loaded devices were easiest to use and provided diagnosable specimens.